Living with a child with autism spectrum disorder: two Sotho mothers’ experiences - Ndlovu, Kaizer Witty (University of the Free State, 2021)
Autism spectrum disorder (ASD) is a developmental disorder that affects individuals’ social, emotional, and communication. Raising a child with ASD is challenging for families, especially the mothers as primary caregivers. This study aimed to explore and describe two Sotho mothers' experiences of living with a child with ASD. The study was qualitative and phenomenological in nature. Semi-structured interviews were conducted with two Sotho mothers living with an ASD- diagnosed child. Thematic analysis was used to analyse the data collected from the interviews. A biopsychosocial-spiritual model (BPSS) was used as the underpinning theory of this study. The findings revealed both the negative and positive experiences of these two Sotho mothers. The study showed that the negative experiences of the mothers could be ascribed to a lack of knowledge and understanding of ASD-related issues, schooling issues, the challenge of managing the child's symptoms, and poor social support. On the other hand, the mothers' positive attitude and acceptance of the children's diagnosis positively impacted their experiences. The study also highlighted that despite the myriad of challenges with which the Sotho mothers had to cope, they continued to appreciate and support their ASD-diagnosed children. It was evident that cultural sensitivity and the lived experiences of mothers need to be taken into account in the diagnosis and treatment of ASD. This research adds to the body of knowledge about the experiences of mothers living with a child with ASD. There is a need for further research about the experiences of mothers and families living with a child with ASD, especially within indigenous communities.
Dissertation (M.Soc.Sc. (Clinical Psychology))--University of the Free State, 2021
Keywords: Autism spectrum disorder; Culture; Experiences; Mothers; Sotho; Autism spectrum disorder (ASD)